Dynamics of high Weber number drops impacting on hydrophobic surfaces with closed micro-cells. Issue 26 (16th June 2016) - Zhang, Rui; Hao, Pengfei; Zhang, Xiwen; He, Feng
Abstract : We demonstrate the good water-repellency of closed micro-structures against high Weber number impacts due to the central air bubble ring. Abstract : The impact dynamics and bouncing performance of high Weber number drops on hydrophobic surfaces with open and closed micro-cells are investigated. Central wetted rings are observed on both closed-cell and open-cell surfaces under high Weber number collisions, which are proposed to constitute the key element affecting the bouncing behaviour. It is found that the drops rebound on closed-cell surfaces where the central area is in the "hybrid wetting state" at high Weber numbers, while the drops adhere to the open-cell surfaces where the central region is in the Wenzel state. A theoretical model is developed to explain this interesting phenomenon, in which the liquid cannot reach the bottom of the closed-cell hydrophobic surfaces since the air stored in micro-cavities prevents the sliding motion of the liquid film and functions as a "gas spring" lifting the liquid lamella. This indicates that the hydrophobic surface with simple micro cavities can maintain the water-repellent characteristics under drop impacts at high Weber numbers. These findings are expected to be crucial to a fundamental understanding of the rapid collisions between drops and micro-structured surfaces, as well as a valuable strategy to guide the fabrication of novel super water-repellant and anti-icing surfaces.